2017
DOI: 10.1039/c7md00434f
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and preliminary antimicrobial evaluation of N-alkyl chain-tethered C-5 functionalized bis-isatins

Abstract: A series of N-alkyl tethered C-5 functionalized bis-isatins were synthesized and evaluated for antimicrobial activity against pathogenic microorganisms. The preliminary evaluation studies revealed the compound 4t, with an optimal combination of bromo-substituent at the C-5 position of isatin ring along with propyl chain linker being most active among the synthesized series exhibiting an IC50 value of 3.72 μM against Trichomonas vaginalis while 4j exhibited an IC50 value of 14.8 μM against Naegleria fowleri, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The majority of alkyl‐tethered isatin dimers 41 (Figure 8) were active against T. vaginalis and Giardia lamblia ( G. lamblia ) with 80.69–100% growth inhibitory at the concentration of 50 μM, but all of them except compounds 41a–c were inactive against Entamoeba histolytica ( E. histolytica ). [ 97 ] Among them, dimer 41c with 100% growth inhibitory against T. vaginalis, G. lamblia , and E. histolytica at the concentration of 50 μM was also active against Naegleria fowleri ( N. fowleri ), and the activity (IC 50 : 14.8 μM) was 3.6 times higher than that of miltefosine (IC 50 : 54.5 μM) against N. fowleri .…”
Section: Antiprotozoal and Antiviral Activitymentioning
confidence: 99%
“…The majority of alkyl‐tethered isatin dimers 41 (Figure 8) were active against T. vaginalis and Giardia lamblia ( G. lamblia ) with 80.69–100% growth inhibitory at the concentration of 50 μM, but all of them except compounds 41a–c were inactive against Entamoeba histolytica ( E. histolytica ). [ 97 ] Among them, dimer 41c with 100% growth inhibitory against T. vaginalis, G. lamblia , and E. histolytica at the concentration of 50 μM was also active against Naegleria fowleri ( N. fowleri ), and the activity (IC 50 : 14.8 μM) was 3.6 times higher than that of miltefosine (IC 50 : 54.5 μM) against N. fowleri .…”
Section: Antiprotozoal and Antiviral Activitymentioning
confidence: 99%
“…Dimeric compounds usually display some unique properties such as enhanced biological activities, compared with their corresponding monomeric counterparts . Isatin dimers have demonstrated interesting biological profiles , therefore they are attractive building blocks for development of new anti‐TB agents.…”
Section: Isatin Dimersmentioning
confidence: 99%
“…Recently, isatin dimers were found to possess promising anticancer potential and have been widely studied . The structure–activity relationship (SAR) revealed that the linker and the noncovalent interactions are crucial for the biological activities of isatin dimers . 1,2,3‐Triazole and tetraethylene glycol can exert various noncovalent interactions, so the isatin dimers tethered through 1,2,3‐triazole‐tetraethylene glycol may have promising anticancer activity.…”
Section: Introductionmentioning
confidence: 99%